2013
DOI: 10.1038/ki.2012.423
|View full text |Cite
|
Sign up to set email alerts
|

Netrin-1 regulates the inflammatory response of neutrophils and macrophages, and suppresses ischemic acute kidney injury by inhibiting COX-2-mediated PGE2 production

Abstract: Netrin-1 regulates inflammation but the mechanism by which this occurs is unknown. Here we explore the role of netrin-1 in regulating the production of the prostanoid metabolite PGE2 from neutrophils in in vitro and in vivo disease models. Ischemia reperfusion in wild-type and RAG-1 knockout mice induced severe kidney injury that was associated with a large increase in neutrophil infiltration and COX-2 expression in the infiltrating leukocytes. Administration of netrin-1 suppressed COX-2 expression, PGE2 and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
93
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 39 publications
1
93
1
Order By: Relevance
“…Among the inflammatory mediators, PGE2 has a known role in mediating the inflammatory response in various kidney injuries [11, 12, 33, 34]. Blockade of PGE2 production by inhibiting its synthetic enzymes of COX-2 or mPGES-1 could improve many kidney diseases in animals [19, 24, 35-37], suggesting a pathogenic role of COX-2/mPGES-1/ PGE2 pathway in kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…Among the inflammatory mediators, PGE2 has a known role in mediating the inflammatory response in various kidney injuries [11, 12, 33, 34]. Blockade of PGE2 production by inhibiting its synthetic enzymes of COX-2 or mPGES-1 could improve many kidney diseases in animals [19, 24, 35-37], suggesting a pathogenic role of COX-2/mPGES-1/ PGE2 pathway in kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…Netrin-1 was the first to be purified and is the best-characterized member. In addition to its involvement in guiding axon migration during embryonic development, netrin-1 functions in organ formation [3][4][5][6] , tumorigenesis [7] , inflammation [8,9] , and anti-apoptotis [10] , as well as being a potential biomarker for renal injury and certain cancers [11,12] . It also promotes the recovery of neuronal function after cerebral ischemia in animal models [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…Adoptive transfer of these genetically modified macrophages preserved kidney function and reduced microvascular platelet deposition in mice with IRI (32). Ranganathan et al found that netrin-1 induced anti-inflammatory M2 macrophage polarization in vitro through activating peroxisome proliferator-activated receptor gamma (PPAR␥)-dependent pathways (104). Adoptive transfer of netrin-1-treated macrophages suppressed inflammation and protected against kidney injury in IRI mice (105).…”
Section: Anti-inflammatory Macrophages Mediate Kidney Repair and Regementioning
confidence: 99%
“…Acute kidney injury caused by ischemia reperfusion or cytotoxic drugs triggers a prominent infiltrate of neutrophils and natural killer cells within hours of tissue injury (72,78,93,104). Monocytes infiltrate the injured kidney shortly after neutrophils, differentiate into macrophages, and contribute to early tubular injury (3).…”
Section: Pro-inflammatory Macrophages Contribute To Kidney Injury Andmentioning
confidence: 99%